PERSONAL GARANSI SEBAGAI JAMINAN PELUNASAN HUTANG DEBITUR KEPADA KREDITUR BEDASARKAN PUTUSAN NOMOR 173/PDT.SUS-PKPU/2019/PN NIAGA.JKT.PST - Putra, Dwi Yanri; Sucondro, Bambang (Tribuere, 2023)
In credit agreements entered into by debtors with creditors, there is a principle of providing credit facilities by providing collateral other than material collateral, namely collateral guarantees, better known as personal guarantees, which means that there is a third party outside the credit agreement who guarantees that the debtor will fulfill all forms of obligations, namely to pay off "the debt is in the credit agreement, one of which can be seen in Decision Number 173/Pdt.Sus-PKPU/2019/PN Niaga.Jkt.Pst." The problem studied in this thesis is how positive legal provisions in Indonesia regarding personal guarantees as credit facilities are provided by creditors to debtors and how to resolve the execution of personal guarantees between creditors and guarantors. The type of research used is normative juridical research, which means reviewing legal regulations to address the problems faced. The results of this research show that based on court decision number 173/Pdt.Sus-PKPU/2019/PN Niaga.Jkt.Pst, it is permissible to apply for a personal guarantee and also resolve problems when a negligent debtor does not pay. The guarantor requests that the debtor's assets be confiscated and auctioned to pay off the debt.